Profiling teachers' sense of professional identity - Canrinus, Esther T.; Helms-Lorenz, Michelle; Beijaard, Douwe; Buitink, Jaap; Hofman, Adriaan (Educational studies, 2011)
This study shows that professional identity should not be viewed as a composed variable with a uniform structure. Based on the literature and previous research, we view teachers' job satisfaction, self-efficacy, occupational commitment and change in the level of motivation as indicators of teachers' professional identity. Using two-step cluster analysis, three distinct professional identity profiles have empirically been identified, based on data of 1214 teachers working in secondary education in the Netherlands. These profiles differed significantly regarding the indicators of teachers' professional identity. Teachers belonging to the found profiles did not significantly differ in their amount of experience.